49‐2: Color reproduction in reflective displays: Stacked CMY. Issue 1 (25th September 2020) - Henzen, Alex; Zhou, Guofu; Zhong, Benpeng
Abstract : E‐paper technology has evolved slowly since the introduction of monochrome electrophoretic displays, particularly in the field of color reproduction and video frame rate. However, in order to achieve a reasonable reflectance, sacrifices had to be made to chromaticity gamut. Using electrowetting stacked CMY technology as reference, the performance of reflective displays is evaluated, and various advanced configurations are demonstrated.